Death process for women who experience abortion from a nursing perspective (Research, Society and Development, 2021)
Introduction: Abortion is the interruption of pregnancy spontaneously or induced. It is considered a delicate topic for embrace cultural, religious, legal, and moral issues. Justification: There are few academic studies on the subject, which makes the research essential. Objective: To understand the process of death through the eyes of women who experience abortion and analyze nursing care for the caused consequences. Methodology: Descriptive and qualitative integrative review. Inclusion criteria were: complete articles, in Portuguese, with a 10-year time frame. Exclusion criteria were: duplicated articles that deviate from the proposed theme. 05 articles were selected for reading and conducting the research. Discussion: Economic restrictions, personal goals, family non-acceptance, absence of a partner, and domestic violence can lead to abortion. Studies reveal that brown or black women had a high rate of induced abortions than white women. The lack of information and judgment makes these women not find a way to interpret their feelings and overcome the loss, which can lead them to a life of self-punishment, risk of depression and addictions, due to the trauma of the experience. The nurse, being the one who has the first contact with the patient, can suggest that she be referred to the psychologist so that she can have the necessary follow-up. Conclusion: Preserve women's lives as well as mental health is a public health issue that will depend directly on the support we will give, regardless of personal issues, care should be complete, universal, and always aiming at the principles of humanization.